The writings of Padraic Colum
1 online resource.
Keywords: "This co-edited collection breaks new ground by bringing together several leading scholars to explore the substantial body of work produced by Padraic Colum (1881-1972) who was a poet, a novelist, a dramatist, a biographer, a writer of fiction for adults and children, and a collector of folklore. The awards, honours and distinction conferred upon him and his work throughout his life and career, as well as retrospectively, give an indication of the significant and wide-ranging appeal and influence of Colum not only as an Irish writer and storyteller but also as a literary figure entrusted with the myths and legends of other cultures and nations. Despite such achievements, he has received comparatively little critical or scholarly attention to date. This volume showcases the richness of Colum's work by subjecting it to a rigorous literary and theoretical examination and is the first combined and detailed analysis of both his children's and adult texts"--